Impact of polyphenols on heart failure and cardiac hypertrophy: clinical effects and molecular mechanisms - Hedayati, Neda; Yaghoobi, Alireza; Salami, Marziyeh; Gholinezhad, Yasaman; Aghadavood, Farnaz; Eshraghi, Reza; Aarabi, Mohammad-Hossein; Homayoonfal, Mina; Asemi, Zatollah; Mirzaei, Hamed; Hajijafari, Mohammad; Mafi, Alireza; et al. (Frontiers in Cardiovascular Medicine, 2023)
Polyphenols are abundant in regular diets and possess antioxidant, anti-inflammatory, anti-cancer, neuroprotective, and cardioprotective effects. Regarding the inadequacy of the current treatments in preventing cardiac remodeling following cardiovascular diseases, attention has been focused on improving cardiac function with potential alternatives such as polyphenols. The following online databases were searched for relevant orginial published from 2000 to 2023: EMBASE, MEDLINE, and Web of Science databases. The search strategy aimed to assess the effects of polyphenols on heart failure and keywords were “heart failure” and “polyphenols” and “cardiac hypertrophy” and “molecular mechanisms”. Our results indicated polyphenols are repeatedly indicated to regulate various heart failure-related vital molecules and signaling pathways, such as inactivating fibrotic and hypertrophic factors, preventing mitochondrial dysfunction and free radical production, the underlying causes of apoptosis, and also improving lipid profile and cellular metabolism. In the current study, we aimed to review the most recent literature and investigations on the underlying mechanism of actions of different polyphenols subclasses in cardiac hypertrophy and heart failure to provide deep insight into novel mechanistic treatments and direct future studies in this context. Moreover, due to polyphenols' low bioavailability from conventional oral and intravenous administration routes, in this study, we have also investigated the currently accessible nano-drug delivery methods to optimize the treatment outcomes by providing sufficient drug delivery, targeted therapy, and less off-target effects, as desired by precision medicine standards.